Embracing diversity: inputs for a strategy to support community seedbanks in South Africa’s smallholder farming areas: Report of field visits to Limpopo and Eastern Cape - Vernooy, Ronnie; Sthapit, B.; Tjikana, Thabo T.; Dibiloane, A.; Maluleke, Nkat Lettie; Mukoma, T.; Bioversity International (2013)
This report presents the findings of a field mission to Limpopo and Eastern Cape provinces of the Republic of South Africa. The mission aimed to assess the viability of establishing and supporting community seed banks in the country’s smallholder farming areas. Tools used included four cell analysis, seed network mapping, seed survey and historical trend analysis. The report recommends establishing pilot community seed banks in each province backed up by sound management and monitoring plans.